1973
DOI: 10.1111/j.1348-0421.1973.tb00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Mixing of Vesicular Stomatitis Virus with HVJ (Sendai Virus)

Abstract: Vesicular stomatitis virus (VSV) plaque-forming virions obtained from mixed infection of HeLa cells with VSV and HVJ (Sendai virus) were shown to contain two types of phenotypically mixed virions : virions doubly neutralizable with both anti-VSV and anti-HVJ antisera (up to 15%), and virions which could be neutralized only with anti-HVJ serum and not with anti-VSV serum (up to 0.3%). No evidence for genetic recombination was obtained between these two viruses. Phenotypically mixed virions could adsorb to and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…However, strong neutralization occurred when the assay was carried out with a mixture of the two sera (Zavada and Rosenbergova, 1972). Similar observations were made with phenotypically mixed virions of VSV and Sendai virus (Kimura, 1973) and VSV and measles virus (Wild et al, 1975(Wild et al, -1976.…”
Section: Additive and Synergistic Effects In Neutralizationsupporting
confidence: 67%
See 1 more Smart Citation
“…However, strong neutralization occurred when the assay was carried out with a mixture of the two sera (Zavada and Rosenbergova, 1972). Similar observations were made with phenotypically mixed virions of VSV and Sendai virus (Kimura, 1973) and VSV and measles virus (Wild et al, 1975(Wild et al, -1976.…”
Section: Additive and Synergistic Effects In Neutralizationsupporting
confidence: 67%
“…Incorporation of influenza virus HA molecules on phenotypically mixed SIV virions, furthermore, renders the virions susceptible to neutralization by antibodies against influenza HA (Vzorov and Compans, 2000). This was also observed for phenotypically mixed virions of VSV with FPV, Sendai, and measles virus (Kimura, 1973;Wild et al, 1975Wild et al, -1976Zavada and Rosenbergova, 1972), as discussed above.…”
Section: Neutralization By Antibodies Against Host Cell-derived Prmentioning
confidence: 75%
“…Even viruses specifi cally targeting cells infected with another virus can be generated (Mebatsion et al 1997 ;Schnell et al 1997 ). Natural paramyxoviruses have been long known for phenotypic mixing, or formation of pseudo-type viruses in coinfections (Kimura 1973 ), and are similarly amenable to artifi cial envelope swapping (for a recent paper, see Mourez et al 2011 ). However, the requirements for incorporation of heterologous envelope proteins may differ for viruses.…”
Section: Envelope Switchingmentioning
confidence: 99%
“…It was concluded that SV-F-beyond its well-characterized membrane fusion property-also functions as a ligand for the hepatocyte-specific ASGP-R (3,19), since it exhibits suitable carbohydrate structures for the interaction with the ASGP-R. A potential pseudotype formation between MoMLV and SV has not been investigated yet. However, formation of stable pseudotypes between vesicular stomatitis virus (VSV) and SV (15) or the closely related SV5 (6) was demonstrated a long time ago. Since pseudotype formation between MoMLV and VSV (35) as well as between VSV and SV has been documented, it was tempting to speculate that pseudotype formation between MoMLV and SV could also take place.…”
mentioning
confidence: 99%
“…For detection of SV-F mRNA by RT-PCR, total cellular RNA was extracted by the method of Chomczynski and Sacchi (5). First-strand cDNA was synthesized by Super Script II reverse transcriptase (Life Technologies, Eggenstein, Germany) from 2 g of total RNA using 25 ng of oligo(dT) [12][13][14][15][16][17][18] primer per l and 200 U of Super Script II per reaction. Primer sequences for SV-F (forward primer, 5ЈTTGTGTTGAGTCC AGATTGACC3Ј; reverse primer, 5ЈATATGTGTCCCTCGG TATACGG3Ј) and murine histone 3.3a (forward primer, 5ЈC CACTGAACTTCTGATCCGC3Ј; reverse primer, 5ЈGCGTG CTAGCTGGATATCTT3Ј) were designed by retrieving published sequence information for the SV-F gene (SV strain Fushimi; sequence identification [ID], PAMSNDFP) and murine histone 3.3a gene (sequence ID, MMZ85979) from the EMBL databases (European Molecular Biology Laboratories, Heidelberg, Germany).…”
mentioning
confidence: 99%